Intergenerational technology adoption barriers in Indonesian family-owned MSME: A multi-level structural equation modeling analysis - Enina Putri; Sabar Aritonang Rajaguguk (Privietlab, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (MSME) in Indonesia faces unique challenges in family owned businesses, where intergenerational dynamics significantly influence technology adoption decisions. This study examines how generational differences create barriers to technology adoption in Indonesian family owned MSME using a multilevel structural equation modeling approach. Using a multi-generational dyadic design with 350 family owned MSME representatives from two or more generations (N=700), we investigated the relationships between generational gaps, family harmony, and digital adoption intentions. Data were collected through structured interviews across traditional industries including textiles, food processing, and handicrafts. The results revealed that family harmony significantly mediates the relationship between generational gaps and technology adoption intentions (β=0.42, p<0.001), while communication quality moderates this relationship (β=0.28, p<0.01). Younger generations’ technology advocacy proves more effective when combined with respect for older decision-making authority, suggesting that successful digital transformation requires culturally sensitive approaches that honor traditional family hierarchies while embracing technological innovation. This study contributes a theoretically grounded framework for understanding technology adoption in family businesses within collectivist cultures, offering practical implications for policymakers and business consultants in designing digital transformation programs for MSME.